Communication guidelines for the nurses caring for patients diagnosed with tuberculosis - Kamenye, Esther; Iipinge, Scholastika; Van Dyk, Agnes (International Journal of Health, 2016)
The purpose of this article is to describe the communication guidelines for the nurses who are caring for patients diagnosed with tuberculosis. A quantitative, exploratory, descriptive, and contextual approach was conducted to explore and describe how nurses communicate with patients diagnosed with tuberculosis at public health facilities in the Khomas region of Namibia. The findings revealed that the nurses caring for patients diagnosed with tuberculosis at public health facilities in the Khomas Region of Namibia exhibited inadequate communication skills. Based on these findings, the guidelines were developed to enhance the communication skills of the nurses who are caring for patients diagnosed with tuberculosis. These guidelines may be implemented in the health facilities that are providing tuberculosis treatment namely: hospitals, health centres, clinics and DOTs points.